Turning Crisis into Opportunity: - Teerawatsakul, Patchaya (Yammy) (2013)

(untitled)
Since sustainability concept was developed, sustainability has not been able to evolve and become a mainstream practice. OgilvyEarth (OE) aims to bridge sustainability with mainstream business but it has recently faced challenges to its business viability. The objective of this paper is to develop a strategy for OE to turnaround its business and prove the viability of sustainable business. This paper assessed and evaluated OE’s strategic position based on secondary and primary data from work placement with OE. While the overall market condition is beneficial for sustainability, OE’s lack of visibility and reputation and disconnection with Ogilvy network and online media result in its underperformance. The recommendations for OE are to network with Ogilvy network, improve its online media channels, attending conferences, and better CRM. The foundations are team capacity and capability restructure and becoming a thought leader. The findings and recommendation can be generalised to apply for other sustainability company to improve performances and become mainstream.